2020
DOI: 10.1002/dta.2754
|View full text |Cite
|
Sign up to set email alerts
|

Segmental analysis of antidepressant and antipsychotic drugs in the hair of schizophrenic patients

Abstract: Hair analysis is useful for documenting long‐term exposure to drugs. The potential of hair analysis for therapeutic drug monitoring within the forensic field has been studied, but reference values for some antidepressants and antipsychotics in the hair of individuals undergoing chronic therapy are still lacking. In the present study, a method was developed and validated for the determination of 23 analytes, including antidepressants, antipsychotics, and related metabolites, in human hair by liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Similar findings were observed for methadone, quetiapine, risperidone, and tramadol [27,31,39,85]. Other studies revealed only small variations in the MD ratios in all hair segments, from the proximal end to the distal end, for patients with a presumed long-term intake of either aripiprazole, chlorprothixene, or clozapine [31,34,35,63]. Similar results were reported for a single dose study of zopiclone in 0.5 cm segments up to four months after ingestion by Hansen et al [63].…”
Section: Inter-and Intraindividual Differencessupporting
confidence: 82%
See 1 more Smart Citation
“…Similar findings were observed for methadone, quetiapine, risperidone, and tramadol [27,31,39,85]. Other studies revealed only small variations in the MD ratios in all hair segments, from the proximal end to the distal end, for patients with a presumed long-term intake of either aripiprazole, chlorprothixene, or clozapine [31,34,35,63]. Similar results were reported for a single dose study of zopiclone in 0.5 cm segments up to four months after ingestion by Hansen et al [63].…”
Section: Inter-and Intraindividual Differencessupporting
confidence: 82%
“…This explains why MD ratios both below and above 1 have been reported. Similar findings were observed for methadone, quetiapine, risperidone, and tramadol [27,31,39,85]. Other studies revealed only small variations in the MD ratios in all hair segments, from the proximal end to the distal end, for patients with a presumed long-term intake of either aripiprazole, chlorprothixene, or clozapine [31,34,35,63].…”
Section: Inter-and Intraindividual Differencessupporting
confidence: 74%
“…Some of these studies proved significant correlations between the dosage and the hair concentration, whereas other authors failed to find significant relationships. Even though such correlations sound promising, many authors suggested that they fail to give a valid estimation of the administered dose as the influence of inter‐individual variations on drug incorporation is too strong 4,37,60 …”
Section: Resultsmentioning
confidence: 99%
“…A greater part of the controlled dose studies was done in the 1990s and early 2000s after which research on controlled dose studies seemed to decrease. The more recent work of Sun et al, 58 Licata et al, 23 and Wang et al 37 is, therefore, a favorable development toward a better understanding and statistical base of concentrations of antidepressants and antipsychotics in human hair. Collaboration with medical stations where patients are treated with antidepressants and antipsychotics serves as a good base for retrospective dose studies with a proper ethical foundation.…”
Section: Resultsmentioning
confidence: 99%
“…The t re atment of hair, gas chromatographymass spectrometer (GCMS) and liquid chromatography tandemmass spectrometry (LCMS/MS) analysis were developed and optimized in scientific research. During the past 30 years, the detection of anabolic steroids in black hair, the drug concentrationtime relationship in hair and a kine tics model were investigated; also, the identification and evaluation system of psychoactive substances in hair was established [8][9][10][11][12][13][14][15][16][17][18][19][20]. Then, information related to whether the subject took the drug or not, the type of drug and the drug ingestion history were provided in casework in judicial practice.…”
Section: Introductionmentioning
confidence: 99%